보중익기탕(補中益氣湯)이 streptozotocin 유발 당뇨병성 위부전마비 백서에 미치는 영향 - 강윤미; Yun-mi Kang; 김효정; Hyo-jung Kim; 박윤범; Yun-beom Park; 정찬문; Chan-mun Jeong; 함성호; Seong-ho Ham; 양웅모; Woong-mo Yang; et al. (大韓本草學會誌, 2019)
Objective : Diabetic gastroparesis is a complication that is defined as delayed gastric emptying and upper gastrointestinal symptoms and often occurs in long-standing diabetic patients. Bojungikgi-tang (BJT) is a traditional oriental herbal formula that has long been used for the treatment of digestive disorders. The purpose of this study was to investigate the effects of BJT on streptozotocin (STZ)-induced diabetic gastroparesis rat model. Methods : Sprague-Dawley (SD) male rats (250-270g) were divided into 13 groups including normal group, STZinduced diabetic control group, BJT diet (7 various concentrations), and insulin-, glibenclamide-, metformintreated group were used for the experiments for the comparison. Diabetic gastroparesis was induced by intraperitoneal injection of STZ. The water intake, food intake, body weights and fasting blood glucose levels were measured. After 4 weeks the animals were sacrificed and gastrin, leptin, insulin, hemoglobin A1C (HbA1c), lactate, lactate dehydrogenase (LDH), bilirubin, creatinine, albumin and lipid levels were evaluated. Results : Intraperitoneal injection of BJT for 4 weeks resulted in increased levels of gastrin in blood and decreased leptin and lactate concentration in STZ-induced diabetic gastroparesis rat model. BJT did not affect insulin, fasting glucose, HbA1c, and lipid levels in STZ-induced diabetic gastroparesis rat model. Conclusion : These results indicated that BJT would have protect effect on diabetic gastroparesis through the improvement effect of gastric motility and fatigue syndrome in STZ-induced diabetic rats. This study shows that BJT might be effective for treatment of diabetes and its complications such as gastroparesis.